The traits of the changes of the matchematics teaching in the V–X forms - Cibulskaitė, Nijolė; Valatkevičienė , Jūratė (Lietuvos matematikos rinkinys, 2021)
The research deals with the analysis of the mathematics teaching situation and his change in the main school during the period from 2003/2004 to 2006/2007 school years. The data of 1177 students of V–X formers in 2006/2007 s.y. were analyzed and compared with the data of 912 students of V–X formers in 2003/2004 s.y. The aims of this research were to ascertain the traits of present mathematics teaching of V–X formers and to compare this results with the results of the formerly research. The research results let draw the conclusions: – mathematics teachers applied such traditionalmethods as independentwork, self-control,work with visual manuals; the importance of the independentwork was decreased; – the frequency of the student‘swork with computers and the project‘smaking is increasing now; – considering peculiarities of human behaviour of teenagers, teachers should be recommended to pay more attention to student‘s interests and emotions in the classroom and to fostering student‘s self respect, particulary in the IX–X forms.